Peran Chitosan sebagai Pemacu Pertumbuhan Kultur Anggrek Dendrobium lasianthera J.J.Sm. secara in vitro - Verena Agustini; Irma Rahayu; Leonardo A. Numberi; Ziyadatun Ni’mah (Jurusan Biologi FMIPA Universitas Cenderawasih, 2020)
The effect of chitosan on micropropagation of Dendrobium lasianthera J.J.Sm was observed. The media used was Vacin and Went (VW) modified with the addition of coconut water and given chitosan with several concentrations. The study was conducted at the Plant Tissue Culture Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Cenderawasih University for 6 months, from April to September 2019. Experiments using a Completely Randomized Design (CRD) of 8 treatments with 3 explants in each bottle for total 3 bottle as a replication. The total explants used in this experiment was 72 explants. The concentration of chitosan were 0% , 1%, 5%, 10%, 15%, 20%, 40% and 50% separately. Observation data were analyzed using ANOVA, if there were significant differences followed by DMRT at the 5% level. Observation variables included number and length of roots, number and length of leaves. The results showed that giving chitosan 10% had a maximum effect on the number of roots and number of leaves, 6.67 and 4.67. As for the highest leaf length of 17.43 mm and the longest root length 19.21 mm were in the media with the addition of chitosan concentration of 15%. The observations showed that chitosan had a positive influence on the growth and development of orchids D. lasianthera plantlet in vitro.Keywords : Chitosan, orchid, Vacin and Went, plantlet.